Acute Peripheral Facial Paralysis Masquerading as Bell's Palsy Is the First Presentation of COVID-19 Infection. (30th January 2023) - Chongsuvivatwong, Tabtim; Mueanchoo, Panitta; Sathirapanya, Praewchompoo; Sathirapanya, Pornchai
Abstract : Although Bell's palsy is a common diagnosis of acute isolated peripheral facial palsy (PFP), acute isolated PFP can be the first presentation of various illnesses, including COVID-19 disease. A female with a known history of well-controlled diabetes mellitus presented initially with acute isolated PFP mimicking Bell's palsy. A course of oral prednisolone was given to treat acute PFP. Severe fifth cervical radicular pain, which is unusual for Bell's palsy followed 3 days later. The COVID-19 infection was finally diagnosed by a real-time polymerase chain reaction (RT-PCR) test 15 days after facial paralysis when typical pulmonary infection symptoms developed. Oral favipiravir was given for the treatment of COVID-19 infection, to which the symptoms completely responded. The COVID-19 infection as a cause of acute isolated PFP should be added to the differential diagnosis of acute isolated PFP, albeit without typical pulmonary infection symptoms, particularly during the global pandemic of the infection.